Writing Tips for Economics Research Papers – 2021-2022 Edition - Plamen Nikolov (Institute of Labor Economics (IZA), 2022)
This document summarizes various tips for economics research papers.
Keywords: A30; A39; 330; writing tips; economics; research papers; research studies